2023
DOI: 10.1038/s41431-023-01377-x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the molecular basis of spinal neurofibromatosis type 1

Abstract: Spinal Neurofibromatosis (SNF) is a form of Neurofibromatosis type 1 (NF1) characterized by bilateral neurofibromas involving all spinal roots. The pathogenic mechanisms determining the SNF form are currently unknown. To verify the presence of genetic variants possibly related to SNF or classic NF1, we studied 106 sporadic NF1 and 75 SNF patients using an NGS panel of 286 genes encoding RAS pathway effectors and neurofibromin interactors and evaluated the expression of syndecans (SDC1, SDC2, SDC3, SDC4), the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Besides the complex effects generated by NF1 microdeletions on deregulation of multiple molecular pathways, it appears that the NF1 haploinsufficiency per se, in addition to RAS hyperactivation, directly or indirectly causes a deregulation of genes encoding neurofibromin interactors such as syndecans. It has recently been reported that syndecan SDC2 , SDC3 and SDC4 were found to be hyper-expressed in both NF1 and Spinal Neurofibromatosis (SNF) patients (Bettinaglio et al 2023 ). This complex molecular landscape is difficult to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the complex effects generated by NF1 microdeletions on deregulation of multiple molecular pathways, it appears that the NF1 haploinsufficiency per se, in addition to RAS hyperactivation, directly or indirectly causes a deregulation of genes encoding neurofibromin interactors such as syndecans. It has recently been reported that syndecan SDC2 , SDC3 and SDC4 were found to be hyper-expressed in both NF1 and Spinal Neurofibromatosis (SNF) patients (Bettinaglio et al 2023 ). This complex molecular landscape is difficult to elucidate.…”
Section: Discussionmentioning
confidence: 99%